First report of acifer group of the subgenus Tripodura Townes (Diptera: Chironomidae: Polypedilum) from India, with a new species and updated world checklist - Mukherjee, Bindarika; Ray, Namrata; Mukherjee, Arka; Naskar, Atanu; Banerjee, Dhriti (Zootaxa, 2024)
A new species of the acifer group of the subgenus Tripodura and genus Polypedilum Kieffer is described on the basis of adult male. The acifer species group is recorded firstly from India. The molecular barcoding of the new species is provided. Moreover, molecular phylogeny of all available species of the subgenus Tripodura, along with an Indian key based on adult males of this subgenus have been designed here. Additionally, a world checklist of the subgenus Tripodura has also been furnished in this study.